Kinetic Modeling of Ring Opening Polymerization of Lactones under Microwave Irradiation. Issue 3 (7th December 2021) - López‐Domínguez, Porfirio; Carranco‐Hernández, Nathalie Michelle; Vivaldo‐Lima, Eduardo
Abstract: A kinetic study on the mathematical modeling of polymerization rate and molar mass development in the ring opening bulk polymerization (ROP) of lactones under microwave irradiation (MI), for the production of biodegradable green polymers used in the biomedical sector, is presented. Two modeling approaches, one based on calculation of average properties using a self‐developed code based on the method of moments, and the other one providing calculation of full molar mass distributions with the aid of the Predici software are contrasted. The observed enhancement on polymerization rate under MI is captured well by using a non‐thermal microwave effect modeling approach, namely, a microwave‐enhanced propagation model. The proposed approach is validated with available experimental data for ROP of ε ‐caprolactone, a monomer which can be obtained from biomasses, using benzyl alcohol (BzOH) and stannous octoate (SnOc)2 as initiator and catalyst, respectively, at 150 °C. Seven case studies are analyzed, including ROPs carried out under both conventional heating (CH) and MI. The effect of initiator and alcohol initial concentrations on polymerization rate and molar mass distributions is analyzed. The advantages of using MI in ROP are assessed. Abstract : The first study on microwave‐activated ROP of lactones is presented. Two modeling approaches are built up considering a previously reported kinetic scheme. The first model is based on the method of moments, whereas the second one is implemented in Predici. The effect of initiator, catalyst, and monomer to initiator ratio on polymerization rate and molar mass development is analyzed.